The Effect of PRP on Striae Gravidarum: a Case Report - Wisni, Anggrieni; Palupi, Sekar Sari (Universitas 'Aisyiyah Yogyakarta, 2025)
Striae gravidarum is a common skin concern after pregnancy, characterized by dermal atrophy and changes in color, texture, and elasticity. Platelet Rich Plasma (PRP) is a regenerative treatment that has shown promise in improving skin quality affected by hormonal and mechanical changes postpartum. This case report presents a 26-year-old female patient with striae gravidarum across the abdominal region following her first pregnancy. The patient received a single session of intradermal PRP injection, followed by clinical evaluation one month later. Clinical improvement was noted through both qualitative and quantitative assessments. Visually, there was fading of striae color from dark brown to light brown, surface smoothing, and increased skin elasticity. The modified Sawetz score improved from 10 to 7, while the Davey distribution score remained unchanged at 8. Qualitative evaluation indicated significant aesthetic improvement. This happens because changes in clinical aspects often occur before changes in distribution. A patient satisfaction questionnaire completed after one month showed maximum scores across all domains, reflecting high acceptance and satisfaction with the procedure. No adverse effects were reported. In conclusion, PRP appears to be a safe, well-tolerated, and effective option for early improvement of striae gravidarum. Greater benefits may be expected with multiple sessions. Further studies are recommended to support these findings in broader populations